Credit Supply and Monetary Policy: Identifying the Bank Balance-Sheet Channel with Loan Applications - Gabriel Jiménez; Steven Ongena; José-Luis Peydró; Jesús Saurina (American Economic Review, 2012)
We analyze the impact of monetary policy on the supply of bank credit. Monetary policy affects both loan supply and demand, thus making identification a steep challenge. We therefore analyze a novel, supervisory dataset with loan applications from Spain. Accounting for time-varying firm heterogeneity in loan demand, we find that tighter monetary and worse economic conditions substantially reduce loan granting, especially from banks with lower capital or liquidity ratios; responding to applications for the same loan, weak banks are less likely to grant the loan. Finally, firms cannot offset the resultant credit restriction by applying to other banks.
Keywords: E32; E44; E5; G21; G28; 330